RETURN MIGRATION – REASONS, CONSEQUENCES AND BENEFITS - RAMONA PÎRVU; GHEORGHE AXINTE (Annals of the University of Petrosani: Economics, 2012)
Return migration is probably the aspect of the migration cycle, which was granted the lowest attention, perhaps because most research resources are located in highly developed countries, while most of the returning most returnees return to developing countries. This is especially unfortunate because perceptions about the process of returning to the country of origin and attitudes towards returning migrants have a significant impact on migrants and their host communities. Rollback, sometimes called remigration, is considered by some authors as the final stage of the migration process, which further comprises the step preparation / decision to migrate and actual migration phase or installation of migrant destination country selected.